Busy Boards and Firm Performance: Evidence from Turkey - Öztürkçü Akçay, Aysel; SEVİMLİ ORGUN, Gamze (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The main goal of this research is to examine the correlation between busy boards and firm performance. In this regard, panel data analysis was used to examine the data of 212 non-financial firms that were traded on Borsa Istanbul between 2018 and 2021. Two distinct indicators are used to measure firm performance, the dependent variable of the study: Tobin's Q, which is based on the market, and return on assets (ROA), which is based on accounting. The main independent variable was busy boards, which was indicated by busy boards (BusyComm) and average board membership (AvrgDirectorship). The analysis's findings indicate that, although busy boards and market-based performance (Tobin's Q) are not significantly related, busy boards do positively and significantly affect accounting-based performance (ROA). The conclusions supported the reputation hypothesis that busy managers create value for the firm.